Super cool forces and motion activities with Max Axiom - Biskup, Agnieszka (Graphic library. Science and engineering activity., 2015)
Super Scientist Max Axiom presents step-by-step instructions for conducting a variety of experiments to learn about forces and motion. Includes a glossary and a list of additional resources.